AGRIBUSINESS AGENTS AND USE OF THE TERRITORY IN TRIÂNGULO MINEIRO/ALTO PARANAÍBA (BRAZIL): OF THE MODERN AGRICULTURE OF GRAINS FOR THE RECENT EXPANSION OF SUGARCANE - Pereira, Mirlei Fachini Vicente (Revista do Departamento de Geografia, 2012)
Since the 1970 and 1980, a group of great companies (mostly foreign) that operate in the grain sector (soy and corn) is installed in Triangulo Mineiro/Alto Paranaíba region, and creates, with support of state policies, the conditions of modernization and territorial specialization productive, transforming the Triangulo Mineiro/Alto Paranaíba into main region of modern agribusiness, in Minas Gerais estate (Brazil). Nowadays, new external demands produce the recent expansion of sugarcane cultivation, with the insertion of new agents and substantial reconfiguration of territorial uses, indicating, again, a process of concentration of resources and a situation of territorial instability.